How madly Filipiniana can Rachelle Gerodias get? (Philippine Star, 2018)
Rachelle Gerodias remembers the old LPs back in the '80s. In her grandmother's home where she used to stay, the songs of Ruben Tagalog and Ric Manrique - two legends dubbed Hari ng Kundiman - would play on the turntable and were eventually recorded on little cassette tapes. For more details visit us at UP College of Music Library.